2018
DOI: 10.1116/1.5063294
|View full text |Cite
|
Sign up to set email alerts
|

Broadband UV-assisted thermal annealing of low-k silicon carbonitride films using a C-rich silazane precursor

Abstract: Low-k dielectric silicon carbonitride (SiCxNy) films are deposited by plasma-enhanced chemical vapor deposition using a carbon-rich silazane precursor, N-methyl-aza-2,2,4-trimethylsilacyclopentane (SiC7NH17), at 100 °C. The post-treatments of SiCxNy films are carried out by thermal annealing and a broadband UV-assisted thermal annealing (UV-annealing) at 400 °C for 5 min. Compared to the thermal annealing treatment, UV-annealing can improve both dielectric and mechanical properties of low-k SiCxNy films. Under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Recent studies 15,16 have shown that UV-assisted thermal curing results in changes of the film properties of pristine SiOCH film and SiCN barrier, as summarized in Table I. For the SiCOH film deposited with an organic precursor, UV-assisted thermal curing removes the organic precursor and forms the pores within the film; it also modifies the skeleton structure and enhances film's mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies 15,16 have shown that UV-assisted thermal curing results in changes of the film properties of pristine SiOCH film and SiCN barrier, as summarized in Table I. For the SiCOH film deposited with an organic precursor, UV-assisted thermal curing removes the organic precursor and forms the pores within the film; it also modifies the skeleton structure and enhances film's mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…15 When deposited by a single-source precursor, the SiCN barriers after UV-assisted thermal curing become silicon-rich, associated with a significant decrease in carbon composition. 16 Additionally, UV-assisted thermal curing results in a reduction of film thickness, k value, and density, while Young's modulus is increased due to the enhancement of cross-linking and rearrangement of the film's skeleton structure.…”
Section: Resultsmentioning
confidence: 99%
“…Carbonitride materials have been deposited from a range of precursors: a tungsten imido precursor was used for the CVD of tungsten carbonitride, WC x N y , 21 titanium and zirconium carbonitride films were deposited from titanium( iv ) and zirconium guanidinate precursors respectively via CVD, 22,23 and silicon carbonitride was deposited via plasma-enhanced (PE)CVD from a carbon rich silazane precursor. 24 Though these precursors do deposit the desired carbonitride materials, imido and guanidinate precursors do not contain direct metal–carbon bonds.…”
Section: Introductionmentioning
confidence: 99%
“…5 Among its traditional usages, SiCxNy is employed as an inert protective coating and encapsulation layer for systems operating under harsh chemical and thermal environments due to its elevated hardness (≥ 40 GPa), high thermal shock and radiation resistance, efficient oxidation protection, and good thermal and tribological performance. 1,[6][7][8] SiCxNy has also been incorporated into a number of current and emerging applications in copper (Cu)-based multilevel metallization schemes in for integrated circuitry (IC) devices. 9 For example, it is being used as a diffusion barrier against Cu migration into the surrounding low dielectric constant () materials.…”
Section: Introductionmentioning
confidence: 99%
“…9 For example, it is being used as a diffusion barrier against Cu migration into the surrounding low dielectric constant () materials. 7,10 SiCxNy is also under consideration as a capping layer and etch stop for copper interconnects, either individually or in combination with selective cobalt capping. 11 Additionally, it is currently being explored as a dielectric film for inclusion in metal-oxide-nitride-oxide-silicon (MONOS)-type non-volatile memory devices.…”
Section: Introductionmentioning
confidence: 99%